Spectrum of KV2.1 Dysfunction in KCNB1‐Associated Neurodevelopmental Disorders. Issue 6 (24th October 2019) - Kang, Seok Kyu; Vanoye, Carlos G.; Misra, Sunita N.; Echevarria, Dennis M.; Calhoun, Jeffrey D.; O'Connor, John B.; Fabre, Katarina L.; McKnight, Dianalee; Demmer, Laurie; Goldenberg, Paula; Grote, Lauren E.; Thiffault, Isabelle; et al.
Abstract : Objective: Pathogenic variants in KCNB1, encoding the voltage‐gated potassium channel KV 2.1, are associated with developmental and epileptic encephalopathy (DEE). Previous functional studies on a limited number of KCNB1 variants indicated a range of molecular mechanisms by which variants affect channel function, including loss of voltage sensitivity, loss of ion selectivity, and reduced cell‐surface expression. Methods: We evaluated a series of 17 KCNB1 variants associated with DEE or other neurodevelopmental disorders (NDDs) to rapidly ascertain channel dysfunction using high‐throughput functional assays. Specifically, we investigated the biophysical properties and cell‐surface expression of variant KV 2.1 channels expressed in heterologous cells using high‐throughput automated electrophysiology and immunocytochemistry–flow cytometry. Results: Pathogenic variants exhibited diverse functional defects, including altered current density and shifts in the voltage dependence of activation and/or inactivation, as homotetramers or when coexpressed with wild‐type KV 2.1. Quantification of protein expression also identified variants with reduced total KV 2.1 expression or deficient cell‐surface expression. Interpretation: Our study establishes a platform for rapid screening of KV 2.1 functional defects caused by KCNB1 variants associated with DEE and other NDDs. This will aid in establishing KCNB1 variant pathogenicity and the mechanism of dysfunction, which will enable targeted strategies for therapeutic intervention based on molecular phenotype. ANN NEUROL 2019;86:899–912